A review of international experience in managing energy irrigation nexus. - Mukherji, Aditi; Shah, Tushaar (International Water Management Institute, 2012)
Besides India, there are a few other countries like Mexico, Spain, Pakistan, Bangladesh and China which also make intensive use of groundwater. This highlight reviews groundwater institutions and policies in these countries, with a special focus on the interlinkages between energy and groundwater. It finds that while there are useful lessons from international experience, none of the other countries offer unmetered electricity to farmers as India does. It is this lack of energy accounting and resistance to metering that is at the heart of the invidious energy-irrigation nexus in India.